Production of biodiesel from Jatropha curcas mixed with waste cooking oil assisted by ultrasound - Kusumo F.; Shamsuddin A.H.; Ahmad A.R.; Dharma S.; Milano J.; Silitonga A.S.; Fazril I.; Marzuki H.; Akhiar A.; Sebayang R.; Tambunan B.H. (Institute of Physics Publishing, 2023)
Biodiesel; Fatty acids; Mixtures; Physicochemical properties; Ultrasonics; EN 14214; Free fatty acid; Jatropha curcas; Jatropha Curcas oil; Methyl esters; Standard requirements; Waste cooking oil; Oils and fats